2021
DOI: 10.1016/j.chest.2021.07.565
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Influenza Virus Pneumonia During the Time of Coronovirus-2019 Pandemic

Abstract: Since the beginning of coronarvirus-2019 pandemic, prevention has been the core measure to mitigate the spread of the virus. Prevention measures included universal masking, frequent hand sanitization, and social distancing are among the measures that proved to be effective. However, these measures are also known to be effective against transmission of influenza virus. We hypothesize that during the times of Covid-19 pandemic, the incidence of influenza pneumonias will also decrease. METHODS:We utilized the Jer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our findings are consistent with the Influenza Hospitalization Surveillance Network from the US, which reported influenza-related hospitalizations as 0.8 per 100,000, the lowest since 2005 [ 12 ]. Alshami et al reported their institutional data from New York, describing a decline in influenza positivity from 6.5% to 0.02% during the last six months of 2020, which is in parallel with our findings [ 13 ]. A nationwide Canadian study by Groves et al reported data from a pediatric population that demonstrated a complete absence of influenza-related hospitalizations, intensive care unit admissions, or deaths [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with the Influenza Hospitalization Surveillance Network from the US, which reported influenza-related hospitalizations as 0.8 per 100,000, the lowest since 2005 [ 12 ]. Alshami et al reported their institutional data from New York, describing a decline in influenza positivity from 6.5% to 0.02% during the last six months of 2020, which is in parallel with our findings [ 13 ]. A nationwide Canadian study by Groves et al reported data from a pediatric population that demonstrated a complete absence of influenza-related hospitalizations, intensive care unit admissions, or deaths [ 14 ].…”
Section: Discussionsupporting
confidence: 91%